System kontroli wewnętrznej w bankach a instytucja kontroli zarządczej w jednostkach sektora finansów publicznych - Fedorowicz, Magdalena (Studia Prawa Publicznego, 2018)
The aim of the study is to analyse two selected supervision institutions: the management control in the public finance sector and the internal control system in banks as examples of regulatory and supervision institutions, having regard to their functional similarities in the two areas of financial law: public finance law and financial market law, and banking law. The study was inspired by the desire to answer the question about the essence of internal control in public finance (management control), which shows, at least in terms of the control objectives, many elements characteristic for internal control systems operating in banks. The aim of the article is also to answer the question about the way of understanding the notion of “internal control” under the banking law and public finance law, its essence, objectives, functions, as well as the coherence of the understanding of the objectives and criteria of internal control in the widely understood financial law areas. However, the research objective is also to show the differences between management control and internal control as supervision institutions, which due to the specificity of the controlled financial matters are separate and thereby allow to present the functions of control institutions related to the needs specific to particular areas of the broadly understood financial law and a multi-faceted approach to the most effective use of control institutions.